Errors in anti‐D immunoglobulin administration: retrospective analysis of 15 years of reports to the UK confidential haemovigilance scheme. Issue 7 (13th March 2013) - Bolton‐Maggs, PHB; Davies, T; Poles, D; Cohen, H
<x xml:space="preserve">Abstract</x> Objective To highlight the errors associated with the use of anti‐D immunoglobulin in RhD antigen‐negative women, and their resultant clinical impact during and after pregnancy, and to suggest strategies to reduce these errors. Design Retrospective review of cumulative reporting to the UK confidential haemovigilance scheme, Serious Hazards of Transfusion (SHOT), between 1996 and 2011. Setting Obstetric departments in the UK. Population Mothers who require anti‐D immunoglobulin to prevent RhD sensitisation during pregnancy or after birth. Methods Hospital transfusion teams reported adverse events to the SHOT database. Main outcome measures Reported number of events and their causes, and morbidity and mortality associated with errors. Results In 15 years of reporting, SHOT haemovigilance has shown a total of 1211 errors related to the administration of anti‐D immunoglobulin, particularly regarding omission or late administration (157/249 or 63% reported in 2011). Anti‐D immunoglobulin errors comprised 13.7% (249/1815) of all SHOT reports in 2011. Failure to recognise women who already have RhD sensitisation occurred in 19 cases, and was followed by suboptimal monitoring of the pregnancy. Nine of the infants suffered haemolytic disease of the fetus and newborn (HDFN): one resulted in neonatal death and three required red cell transfusion. Conclusions Babies as well as their mothers remain at risk from avoidable errors. More active attention at national and local levels to further education and training, particularly for midwives, is an absolute necessity. We recommend the use of a SHOT‐devised anti‐D administration flowchart, adapted locally into a checklist, to help reduce errors.